Nanomedicine-Enhanced Radiotherapy for Glioblastoma: Advances in Targeted Therapy and Adaptive Treatment Strategies - Kamila Rawojć; Mansoor M. Ahmed; Ayesha Mukhtiar; Magdalena Łukowiak; Kamil Kisielewicz (Pharmaceutics)
Glioblastoma multiforme remains one of the most aggressive and treatment-resistant brain tumors that necessitate innovative therapeutic approaches. Nanomedicine has emerged as a promising strategy to enhance radiation therapy by improving drug delivery, radiosensitization, and real-time treatment monitoring. Stimuli-responsive nanoparticles can overcome limitations of the blood–brain barrier, modulate tumor microenvironment, and facilitate targeted therapeutic interventions. The integration of nanotechnology with proton and X-ray radiotherapy offers improved dose precision, enhanced radiosensitization, and adaptive treatment strategies. Furthermore, Artificial Intelligence-driven nanoparticle designs are optimizing therapeutic outcomes by tailoring formulations to tumor-specific characteristics. While promising, clinical translation remains a challenge that requires rigorous validation to ensure safety and efficacy. This review highlights advancements in nanomedicine-enhanced radiotherapy and future directions for glioblastoma multiforme treatment.